Pilot Mining Robot for Polymetallic Nodules and Pre-Pilot Mining Tests - Sup Hong (International Marine Minerals Society, 2011)
A pilot mining robot, named MineRo-II, has been developed by KIOST during 2011-2012. The pilot scale was defined as 1/5 of the commercial mining capacity, 1.5 million dry-tons of nodules per year. The development purpose of MineRo-II is to use for the pilot mining test planned in 2015. MineRo-II was designed to be self-propelled by electric-hydraulic power and remotely operated in real-time from aboard. The main operational functions are crawling on seafloor, pick-up and crushing of nodules, discharging nodules out to buffer. Prior to MineRo-II, a test miner (MineRo-I) was developed in scale of 1/20th in 2007, and performed two times sea trials in 2009 and 2010. The results of performance tests were evaluated and utilized for the concept of MineRo-II. The design concept aimed at the expandability of the mining capacity based on modularity of configuration, maintenance simplicity and multiplicity of backup solution. The pilot-scale mining capacity is achieved by four pick-up modules of each 1m wide, which are moving forward with robot vehicle and sweep the nodules entering below the pick-up heads. Principally, by adding the pickup modules in lateral dimension the mining capacity may increase linearly. MineRo-II was designed and constructed in unit-module wise. The robot consists of two unit-modules having an identical mechanical and hydraulic configuration. Each unitmodule has two tracks, two pick-up devices with attitude control devices, two crushers, one discharge pump, and one hydraulic system. Two unit-modules are connected by one loading frame and integrated by electric-electronic system. Two thrusters for control of the